Bladder preservation after radiochemotherapy for muscle invasive bladder cancer - Birkenhake, Stefan (Radiology and oncology (Ljubljana), 1997)
To determine efficacy of radio-chemo-therapy (RTC) with platin-derivatives compared to radiotherapy (RT) alone in patients with bladder cancer. From May '82 to May '96, 333 patients with bladder cancer were treated at the University Hospital of Erlangen, 282 of gh risk T1 (e.g. G3/4, R1/2, N+) bladder cancer, were treated either by radiotherapy (RT) or concomitant radiochemotherapy with platinum deviratives (RCT-Cis or RCT-Carbo) after preceding transurethral resection of bladder (TUR), with curative intent. Median doses of 50.4 Gy and 41.4 Gy in fractions of 1.8 Gy (once a day, 5 times per week) were applied to the bladder and pelvic lymph nodes. 54 patients recived 45 Gy to the paraaortal lymphnodes. 128 patients received irradiation alone, while 205 received it simultaneously with either cisplatin or carboplatin in the 1st and 5th treatment weeks. Uni- and mutivarie analysesweT-category, R-status, and treatment modality on patients' survivalerpreservation. Complete remissions were noted in 56%, 70% and 85% of patients after RT, RCT-Carbo or RTC-Cis, respectively (p<0.05). The strongest impact on CR was exerted by R-status (p<0.0003) and T-category (p<0.0001). 79%of survivors have a functional bladder. Concerning survival, RT, and RTC differed significantly only after univariate analysis. For survival with preserved bladdr, only initial R-status was significant in multivariate analysis (p<0.04). Bladder cancer can be effectively treated by RT/RTC following TURB.
Keywords: Bladder neoplasms; Drug therapy; Platinum; Radioisotopes; Radiotherapy; Treatment outcome